Pengaruh Penggaraman Dan Suhu Penggorengan Terhadap Karakteristik Kimia Dan Sensoris Kerang Ale-Ale (Meretrix Meretrix) Tepung - Zulfahmi, A. Nova; Cholid, Irfan; Assrorudin, Assrorudin; Arianti, Ira (Jurnal Ilmu Pangan dan Hasil Pertanian, 2024)
The background to this research is that ale-ale shellfish are endemic shellfish in Ketapang Regency; the results are abundant because they are available all year round. The use of ale-ale shellfish has yet to be maximized, so it does not have added economic value for the people of Ketapang Regency. The nutrition of ale-ale shellfish is quite a lot from the fatty acids and amino acids contained in ale-ale shellfish. The weakness of ale-ale shellfish is that its water content is very high, so a method is needed to reduce the water content so that it can be used as a raw material for processed products that have high economic value, one of which is ale-ale flour. The raw material in this research is fresh ale-ale shellfish meat added with 0% and 5% salt and fried at 120ËšC, 130ËšC, and 140ËšC for 15 minutes. Tests in this research consisted of tests for protein content, fat content, water content, and sensory tests. The results of this study showed that the water content was the lowest in the P3G3 treatment, namely 5.87%. The addition of salt increases fat and protein levels indirectly. The treatment with the highest fat and protein content was P3G3, namely 1.33% and 6.43%. Sensory parameters show that the addition of salt and differences in the frying temperature of flour ales can increase consumer acceptance. Ale-ale flour with the addition of 5% salt and fried at a temperature of 140ËšC (P3G3) got the highest value in all parameters. The addition of salt and the higher temperature used in processing ale-ale flour can increase the fat and protein content, which consumers like.